Preparation of 1, 3‐Diphenylselenophenotetraazaporphyrinato Ruthenium(II) Bis(4‐methylpyridine) by the Reaction of 3, 4‐Dicyano‐2, 5‐diphenylselenophene and Phthalonitrile: Its Optical and Electrochemical Properties. Issue 5 (23rd May 2014) - Kimura, Takeshi; Murakami, Naoko
ABSTRACT 2, 5‐Diphenylselenophene (2a) was treated with bromine and then copper(I) cyanide to produce 3, 4‐dicyano‐2, 5‐diphenylselenophene (4). Compound 4 was mixed with phthalonitrile, and the mixture was reacted with ruthenium(III) trichloride and 4‐methylpyridine in the presence of 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) in refluxed 2‐ethoxyethanol to give 1, 3‐diphenylselenophenotetraazaporphyrinato ruthenium(II) bis(4‐methylpyridine) (6). The structure of 6 was determined by 1H NMR and fast atom bombardment mass spectrometry (FABMS). In the 1H NMR spectrum, the signals of 4‐methylpyridine coordinating to the central ruthenium atom were observed at a higher magnetic field than those of free 4‐methylpyridine itself but at a lower magnetic field than those of phthaocyaninato ruthenium(II) bis(4‐methylpyridine) (7). The 77Se NMR spectrum of 6 showed one singlet peak at δ = 759.5 ppm, which is a lower magnetic field than those of 2a and 4. The Q band absorption of 6 (λmax = 660 nm) lies at a longer wavelength than does that of 7. Oxidation and reduction potentials of 6 were measured with cyclic voltammetry using Ag/AgNO3 as a reference electrode.